Spintronics III 2010
DOI: 10.1117/12.861552
|View full text |Cite
|
Sign up to set email alerts
|

Injecting, controlling, and storing magnetic domain walls in ferromagnetic nanowires

Abstract: Domain walls in ferromagnetic nanowires are important for proposed devices in recording, logic, and sensing. The realization of such devices depends in part on the ability to quickly and accurately control the domain wall from creation until placement. Using micromagnetic computer simulation we demonstrate how a combination of externally applied magnetic fields is used to quickly inject, move, and accurately place multiple domain walls within a single wire for potential recording and logical operations. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These solutions are outside the separatrix, since the solutions inside the separatrix take theirs values in intervals which sizes is less than π. These solutions satisfy (16)…”
Section: Existence Of Steady-states Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These solutions are outside the separatrix, since the solutions inside the separatrix take theirs values in intervals which sizes is less than π. These solutions satisfy (16)…”
Section: Existence Of Steady-states Solutionsmentioning
confidence: 99%
“…This property plays an important role in numerical data storage since the information is encoded by the localization of DWs (see [2,15,20]). Because of these potential applications, DW dynamics in ferromagnetic wires is intensively investigated as well in Physics (see [16,19,[23][24][25][26][27]) as in Mathematics (see [3,8,10,17,22]). In [12,14,18], DW dynamics and magnetization reversal in ferromagnetic rings are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the transverse field could be applied longer which would allow domain walls to move more than one notch at a time. 25 The technique of using a locally applied transverse field pulse could also be used in the current driven case. In this situation, a current in a ferromagnetic wire would provide the driving force and the local transverse field could be used to select which domain wall to move, similar to the process shown in Fig.…”
Section: -3mentioning
confidence: 99%
“…[21][22][23][24] The ability of the transverse field to change the domain wall speed also impacts the ability of a notch to trap a domain wall, in that fast moving walls can pass a notch that is capable of trapping a slower moving wall. [25][26][27] When the transverse field component is applied parallel to the direction of the magnetic moments within the domain wall, it will speed up, and if applied anti-parallel, it will slow down. 22 Similarly in Fig.…”
mentioning
confidence: 99%